Urgensi Kurikulum Perbankan Syariah Perguruan Tinggi Terhadap Sumber Daya Manusia Industri Perbankan Syariah - Abdul Wahab (TADARUS, 2016)
AbstractIn terms of the development of Islamic banking institutions there are two things that were most significant, namely, curriculum and human resources. In curriculum development of Islamic banking, at least have the competence-based curriculum, must integrate the values of sharia lecture material financial economics comprehensively, the curriculum also ideally equipped with the sciences quantitative, related to the development of reason and logic, as well as integrating between theory and practice , In addition to the curriculum, other things that need to be considered in the development of Islamic financial economic education in the future is their own human assets as a determinant of human success or failure of a program's success.